Actors on the Scene: Immune Cells in the Myeloma Niche - Leone, Patrizia; Solimando, Antonio Giovanni; Malerba, Eleonora; Fasano, Rossella; Buonavoglia, Alessio; Pappagallo, Fabrizio; De Re, Valli; Argentiero, Antonella; Silvestris, Nicola; Vacca, Angelo; Racanelli, Vito (Frontiers in Oncology, 2020)
Two mechanisms are involved in the immune escape of cancer cells: the immunoediting of tumor cells and the suppression of the immune system. Both processes have been revealed in multiple myeloma (MM). Complex interactions between tumor plasma cells and the bone marrow (BM) microenvironment contribute to generate an immunosuppressive milieu characterized by high concentration of immunosuppressive factors, loss of effective antigen presentation, effector cell dysfunction, and expansion of immunosuppressive cell populations, such as myeloid-derived suppressor cells, regulatory T cells and T cells expressing checkpoint molecules such as programmed cell death 1. Considering the great immunosuppressive impact of BM myeloma microenvironment many strategies to overcome it and restore myeloma immunosurveillance have been elaborated. The most successful ones are combined approaches such as checkpoint inhibitors in combination with immunomodulatory drugs, anti-monoclonal antibodies and proteasome inhibitors as well as chimeric antigen receptor (CAR) T cell therapy. How best to combine anti-MM therapies and what is the optimal timing to treat the patient are important questions to be addressed in future trials. Moreover, intratumor MM heterogeneity suggests the crucial importance of tailored therapies to identify patients who might benefit the most from immunotherapy, reaching deeper and more durable responses.